نُظم السّقي التقليدي في الجنوب الغربي الجزائري و انعكاساتها الثقافية - زويني, زهراء; حوتية, محمد (جامعة الوادي - University of Eloued, 2022)
تخضع المياه في الصحراء بمختلف أنواعها سواء تلك التي تجري بها الوديان او تلك التي تستخرج من الآبار لنظام معين في الاستخدام، حتى يتم الاستغلال الأحسن لها باعتبارها مورداً نادراً وثمينا يتوجب التعامل معه بتقنية وحذر من أجل التوزيع العادل بين جميع السكان لتغطية حاجاتهم من ريِّ وشرب .و في هذا السياق تَعرف منطقة الجنوب الغربي الجزائري أنظمة سقي غاية في الدقة والنجاعة. وهذه الدراسة تسلط الضوء على الجانب النظري والتطبيقي لهذه التقنيات من حيث المفاهيم وكيفيه الاستخدام وانعكاساتها على نواحي الحياة . وهو الهدف الذي نصبو لمعالجته من وراء هذه الورقه البحثية ،ومما لاشك فيه أن نُظم السقي التقليدية تٌعتبر العامل الأساسي في المحافظة على لُحمة التجمعات البشرية واستمرارها في الصحراء عامة والجنوب الغربي الجزائري خاصة ، وهي نتيجة من بين أهم النتائج المتوصل إليها في البحث . Waters in the desert are subject to a specific system of use، whether those that run through the valleys or those that are extracted from wells. In order to ensure best exploitation، of said waters as they are considered a rare and valuable resource، it is imperative to carefully and cautiously deal with them، to guarantee a fair distribution among all residents to cover their irrigation and drinking needs. In this context، the southwestern Algerian region knows accurate and successful، watering systems. This study sheds light on the theoretical and practical sides of these techniques in terms of concepts، how to use these techniques and their implications on various aspects of life. Which eventually is this research paper’s aim. It is undoubtable that the traditional watering systems are a key factor in preserving and sustaining human population، the desert in general، and in the southwestern region in particular، which is one of the most important results of the research.
مقال
Keywords: نظام السقي ; حاضرة توات ; الجنوب الغربي ; الإنسان الصحراوي ; الفقارة؛ الجزائر